Efisiensi Teknis Usahatani Cabai Merah Indonesia (Forum Agribisnis, 2025)
The rising price of red chili is associated with the production availability at the farm level. Meanwhile, the price increase has not been sufficient to impact on farmers' income positively. Production problems can not only be explained through production factors but other factors also contribute. Technical efficiency is an analytical method that measures production factors and external factors directly. Spatial measurement may lead to policy bias. Therefore, this study aims to measure and analyze the factors that affect the level of technical efficiency of Indonesian red chili. This study applied the Stochastic Frontier Analysis (SFA) method to measure and analyze the factors affecting the technical efficiency of Indonesian red chili. All production inputs, including seeds, chemical fertilizers, organic fertilizers, pesticides, labor, and harvest areas, affect the improvement of Indonesian red chili production. Inefficiency factors that can increase the level of technical efficiency of red chili are education, technology, farmer groups, planting season, land type, cropping system, and the utilization of certified seeds. While access to credit, cooperative membership, and subsidies can reduce the level of technical efficiency of Indonesian red chili. The average technical efficiency level of Indonesian red chili is 0,6525. A reassessment of subsidy policies and access to credit and development of agricultural institutions are possible policies that could be considered by the government to improve the production and technical efficiency level of Indonesian red chili.